A Simple Wooden Ribosome Model: Helping Students Understand Transpeptidation - Donald A. Klein (American Society for Microbiology, 2010)
In teaching biology, it is critical to communicate broad concepts before considering more specific details of a process. This is particularly important when attempting to communicate the essence of transpeptidation, a key process in translation. Based on my experience in teaching general microbiology, transpeptidation is the most difficult aspect of translation for students to understand. Typically, figures given in microbiology and biochemistry texts show movement of the nascent peptide attached to the P position t-RNA to the incoming single amino acid attached to the A position amino acid-tRNA by the use of arrows, an approach that makes it difficult to understand the dynamic aspects of this process. To attempt to improve understanding of this process, tutorials also are available that emphasize decoding “messages” and the use of “Do-it-Yourself DNA Kits” where the process of transpeptidation is not specifically discussed. The simple model described in this communication provides a clear demonstration of the transpeptidation process.